Hepatoid Adenocarcinoma of the Lung: A Systematic Review of the Literature From 1981 to 2020 - Hou, Zan; Xie, Jiaqing; Zhang, Li; Dai, Gangyi; Chen, Yuanhang; He, Lang (Frontiers in Oncology, 2021)
Abstract Objectives: We report the first case of hepatoid adenocarcinoma of the lung (HAL) with PIK3CA mutation. In addition, we analyzed data from HAL cases over the past 40 years to study its main treatment methods,prognosis,and the relationship between prognosis and the serum alpha-fetoprotein (AFP) level before treatment. Methods: We report a 66-year-old male case who was diagnosed with locally advanced HAL with PIK3CA mutation and carried out a systematic literature search for HAL cases documented between 1981 and 2020. General patient information including case characteristics was extracted and summarized. The median OS (mOS) of HAL patients was determined using the KM survival curve. The Cox proportional hazards regression model was used to evaluate the effect of tumor size, location and serum AFP value before treatment and radical surgery(RS) on the prognosis of patients. Results: A total of 46 studies including 51 HAL patients was included in our review. Our study revealed that 52.9% of tumors were located in the upper lobe of the right lung. The proportion of serum AFP-positive patients before treatment, early stage patients (TNM stage I and II) and patients who had received surgery were 69.2%, 34.1%, and 40%, respectively. The mOS of HAL patients was 16.0 months. The 2-year and 5-year survival rates of the patients were 35.3% and 8.0%, respectively. In the subgroup analysis, the 2-year survival rate for patients who received RS was 62.5%, while for patients who were unable to undergo RS was only 12.5% (p = 0.009). The Cox proportional hazards regression model indicated that RS can significantly improve the prognosis of HAL patients (p = 0.011), although the location and size of tumor as well as the serum AFP value before treatment had no significant effect on their prognosis (p = 0.82, p = 0.96, p = 0.25). Conclusions: HAL patients have a poor prognosis, and the survival benefits for patients receiving chemoradiotherapy or chemotherapy alone appear to be limited. We demonstrate statistically for the first time that pretreatment serum AFP values are not related to the prognosis of HAL patients and RS can significantly improve patient prognosis.